Analysis of the Potential Utilization of Semantok Reservoir For the Fulfillment of Raw Water and Irrigation Water - Augustiman, Yoggie Azhary; Yuliani , Emma; Haribowo , Riyanto (Gema Wiralodra, 2023)
Each reservoir's need for water is increasing, including the Semantok Reservoir. It is intended to provide 312 l/sec of raw water needs and irrigation water for 1,900 acres. To assess whether irrigation water requirements are met, it is important to simulate using the Standard Operating Rule (SOR) technique and the QM For Windows V5 linear program. This simulation model incorporates normal year, dry year, and wet year flow along with monthly mid-month discharge input. The scenario was created using the QM For Windows V5 linear program under 25 year and 50 year circumstances. Simulations based on usual years, dry years, and wet years using the SOR technique and the QM For Windows linear software indicate 100% fulfillment in every year. The water discharge in 2048 in dry years is 0.22 m3/sec, in normal years is 0.31 m3/sec, and in wet years is 0.34 m3/sec, according to the analysis of the QM For Windows V5 linear program by simulating conditions for 25 years and 50 years, while in 2073 in dry years is 0.17 m3/sec, normal year is 0.23 m3/sec, and wet year reaches 0.33 m3/sec, and recommending an increase in.